A Simple Stereological Method for Estimating the Number and the Volume of the Pancreatic Beta Cells - Noorafshan, Ali; Hoseini, Leila; Karbalay-Doust, Saied; Nadimi, Elham (JOP. Journal of the Pancreas, 2012)
Context Number of the beta cells as well as their volume is a fundamental variable in the pancreatic research. Objectives This study describes a simple method for stereological estimation of the volume of the pancreas, the total volume of the islets, and the total number, as well as the mean volume, of the beta cells in rat. Methods The primary volume of the pancreas was measured using the immersion method. Also, tissue shrinkage was estimated and the final pancreas volume was corrected without the need for serial sectioning. A limited number (i.e., 10-13) of the isotropic uniform random slabs of each pancreas was embedded in the same block. One 5 µm and one 20 µm sections were obtained and stained with a modified aldehyde fuchsin. The point counting, optical disector and point-sampled intercept methods were used to estimate the volume density of the islet, the numerical density of the beta cells, and the mean cell volume, respectively. Results After calculating the tissue shrinkage, the mean primary volume of the pancreas (628 mm3; CV: 25%) was corrected to obtain the final volume (442 mm3; CV: 39%). The mean islet volume was reported as 3.8 mm3 (CV: 22%). Besides, the total number of the beta cells was estimated as 2.9x106 (CV: 20%). Moreover, the mean volume of the beta cells was obtained (1,158 µm3; CV: 9%). Conclusions It takes almost one hour to estimate the volume of the islets and two hours to count the cells and estimate the intercepts per animal. Image: Optical scan for estimation of the number of the beta cells.